High-strength high-energy-content high-entropy alloy reaction structure material and preparation method thereof
By designing the element composition and process of high-entropy alloys, high-strength, high-energy and high-density reactive structural materials are formed, which solves the problem of insufficient strength of traditional reactive structural materials, and realizes the characteristics of high strength and high density, which is suitable for engineering application.
Patent Information
- Application Number
- CN202411282670.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-13
AI Technical Summary
Traditional reactive structural materials have problems with low strength and cannot meet the needs of existing projects. Moreover, high-entropy alloys have no high-strength, high energy content and high density materials in related fields.
A high-strength, high-energy, high-entropy alloy reactive structural material, including Ti, Zr, V, Nb and Ta elements, was designed. Through specific elements composition and proportion, magnetic levitation induction smelting and thermal isostatic pressure treatment processes are used to form Single-phase solid solution structure ensures high strength and high density of the material.
It realizes the characteristics of high strength, high activity and high density. The material has high strength and high energy release characteristics under impact loading conditions, and has a uniform internal structure. It has excellent room temperature static and dynamic compression strong plasticity, which is suitable for industrial mass production.
Smart Images

Figure CN119220878A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, and in particular to a high-strength, high-energy, high-entropy alloy reaction structural material and a preparation method thereof. Background Art
[0002] Reactive structural materials refer to materials with certain mechanical properties that can induce high-energy chemical reactions between material components or between components and the environment under certain conditions, releasing heat. Reactive structural materials have the characteristics of structural and energy integration. They are inert at room temperature and pressure. Under extreme conditions, such as impact loading, high temperature and high pressure, reactive structural materials are activated, inducing chemical reactions between component components or between component components and the environment.
[0003] Traditional reactive structural materials can be mainly divided into three types: metal-fluoropolymer, metal-oxide, and metal-metal. Metal-fluoropolymer is a composite material composed of metal components and fluoropolymers, and has the characteristics of high energy density. However, due to the low strength of polymer materials, metal-fluoropolymer reactive structural materials often have low structural strength (less than 100MPa), which makes it difficult to directly meet practical engineering applications. Metal-oxides have problems such as low reaction rate, low actual heat release, and insufficient reaction process during application. Metal-metal reactive structural materials are composed of highly active metals and metal or metalloid elements, and the reaction products are often intermetallic compounds. However, in actual applications, the low mechanical properties, density and compactness of metal active composite materials have been difficult to effectively solve.
[0004] Therefore, traditional reaction structural materials have the disadvantage of low strength, which has not been solved and cannot meet the needs of existing projects.
[0005] Multi-principal element high entropy alloy is a new type of metal material with designable composition and controllable performance developed in recent years. It subverts the traditional alloy design concept of single metal element and is a solid solution alloy formed by fusing multiple elements in equiatomic or near-atomic ratios.
[0006] The design concept of high entropy alloys realizes the "free design" and combination of alloy components at the atomic level. Combined with the adjustment of preparation and heat treatment processes, solid solution materials with excellent comprehensive performance can be obtained. The optimization of the main element can meet the high strength, high energy content, high density and other characteristics required by the reaction structure material.
[0007] Although in theory, high-entropy alloy reaction structural materials with high strength, high energy content and high density can be designed through the design concept of high-entropy alloy, at present, there is still no report of high-entropy alloy reaction structural materials with the above-mentioned related properties. This is mainly because no one has conducted research in the relevant field of existing high-entropy alloys, and no materials with relevant characteristics have appeared. Therefore, there is still a blank of high-entropy alloy reaction structural materials with high strength, high energy content and high density. Summary of the invention
[0008] The purpose of the present invention is to provide a high-strength, high-energy, high-entropy alloy reaction structural material and a preparation method thereof, so as to solve the technical problem that the high-entropy alloy materials produced in the prior art cannot simultaneously meet the high-strength, high-energy, and high-density characteristics.
[0009] In order to solve the above technical problems, the present invention specifically provides the following technical solutions: In a first aspect of the present invention, a high-strength, high-energy, high-entropy alloy reaction structural material is provided, comprising at least two of the elements Ti, Zr, V, Nb and Ta.
[0010] Furthermore, the general formula of the high entropy alloy is TiZrVNbTa, and the content of each element in atomic percentage is as follows: Ti: 0%-25%; Zr: 0%-25%; V: 0%-15%; Nb: 0%-25%; She: 20%-45%.
[0011] Furthermore, the general formula of the high entropy alloy is TiZrVNbTa, and the content of each element in atomic percentage is as follows: Ti: 15%-25%; Zr: 15%-25%; V: 0%-10%; Nb: 15%-25%; She: 30%-40%.
[0012] In a second aspect of the present invention, a method for preparing a high-strength, high-energy, high-entropy alloy reaction structural material is provided, comprising the following steps: Batching: batching clean Ti element particles, Zr element particles, V element particles, Nb element particles and Ta element particles according to the atomic content ratio; Melting: sending the above ingredients to a magnetic levitation induction melting furnace and melting them in a vacuum environment; Hot isostatic pressing: The cast alloy prepared after smelting is subjected to hot isostatic pressing to obtain a high entropy alloy reaction structural material.
[0013] Furthermore, the purity of the Ti element particles is 99.9%, the purity of the Zr element particles is 99.95%, the purity of the V element particles is 99.9%, the purity of the Nb element particles is 99.95%, and the purity of the Ta element particles is 99.95%; Among them, the above-mentioned metal particles are all clean raw materials for removing oxide scale.
[0014] Furthermore, the elements contained in the above metal particles are calculated by atomic percentage: Ti: 15%-25%; Zr: 15%-25%; V: 0%-10%; Nb: 15%-25%; She: 30%-40%.
[0015] Furthermore, during alloy smelting, the raw materials are fed in the following feeding order: First, Ti and Zr elements are synthesized into TiZr master alloy, and Nb and Ta elements are synthesized into NbTa master alloy; Then, the TiZr master alloy, the NbTa master alloy and a small amount of V element are melted to form a single-phase solid solution structure.
[0016] Furthermore, the above smelting step is specifically as follows: at 10 -3 The alloy is melted 4-6 times under a vacuum environment of Pa, each melting temperature is between 2200℃ and 2300℃, and each melting time is 15-20 minutes. After the alloy composition is uniform, it is poured into a mold and cooled naturally under a vacuum protection environment.
[0017] Furthermore, the hot isostatic pressing step is carried out in a vacuum or inert gas protected atmosphere, the hot isostatic pressing temperature is 1150-1250° C., and the holding time is 4-6 hours.
[0018] Furthermore, the hot isostatic pressing pressure is 180-200 MPa, the holding time is 4-6 hours, and the cooling rate is 50°C / min.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The high entropy alloy reaction structure material provided by the present invention realizes a single-phase solid solution structure of Ti, Zr, V, Nb, and Ta elements through a special element composition and a special ratio relationship, especially the introduction of the V element and the regulation of the V element content, and exhibits the characteristics of high activity and high strength plasticity. At the same time, the alloy density is significantly higher than that of existing reaction structure materials. Due to the active element design, the high entropy alloy reaction structure material has the characteristics of high strength, high activity and high density.
[0020] 2. The high entropy alloy preparation method provided by the present invention fully combines the particularity of the elements contained in the high entropy alloy and the particularity of the atomic content between the elements, adopts a special feeding order, first generates TiZr master alloy and NbTa master alloy respectively, and then melts with a small amount of V element to form a single-phase solid solution structure, and performs hot isostatic pressing. Under specific melting conditions and static pressing conditions, the alloy is a single-phase BCC structure, has high strength and high energy release characteristics under impact loading conditions, and its internal organization structure is uniform, and has excellent room temperature static and dynamic compression strength and plasticity. Due to the active element design, the alloy also has the characteristics of high density, high strength and high energy content, the process is simple, safe and reliable, and the magnetic suspension melting process adopted makes the material have good density and phase structure stability, which is easy to industrialize and mass produce. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0022] Figure 1 This is a physical picture of the high entropy alloy ingot of the present invention; Figure 2 This is the energy release overpressure diagram of the high entropy alloy of the first embodiment of the present invention; Figure 3 It is a static and dynamic mechanical performance diagram of the first embodiment of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Traditional reaction structural materials have the disadvantage of low strength, which has not been solved and cannot meet the needs of existing projects.
[0025] Although in theory, high-entropy alloy reaction structural materials with high strength, high energy content and high density can be designed through the design concept of high-entropy alloy, at present, there is still no report of high-entropy alloy reaction structural materials with the above-mentioned related properties. This is mainly because no one has conducted research in the relevant field of existing high-entropy alloys, and no materials with relevant characteristics have appeared. Therefore, there is still a blank of high-entropy alloy reaction structural materials with high strength, high energy content and high density.
[0026] The difficulty in using the design concept of high entropy alloys to design high entropy alloys with high strength, high energy content and high density lies in how to design the composition of the elements inside the high entropy alloy, and how to design the atomic ratio between the elements based on the element composition, so that the high entropy alloy can have high strength, high energy content and high density at the same time.
[0027] like Figure 1 As shown, the present invention provides a high-strength, high-energy, high-entropy alloy reaction structural material, including at least two of Ti, Zr, V, Nb and Ta elements.
[0028] The general formula of the high entropy alloy is TiZrVNbTa, and the content of each element in atomic percentage is as follows: Ti: 0%-25%; Zr: 0%-25%; V: 0%-15%; Nb: 0%-25%; She: 20%-45%.
[0029] The general formula of the high entropy alloy is TiZrVNbTa, and the content of each element in atomic percentage is as follows: Ti: 15%-25%; Zr: 15%-25%; V: 0%-10%; Nb: 15%-25%; She: 30%-40%.
[0030] High strength requires reasonable V content control. Low V content means lower strength. However, when V content is high, brittle intermetallic compound phases are very likely to appear, making the overall material brittle and difficult to use in actual engineering. Therefore, the ratio between V content and other elements is the key and difficulty in controlling alloy strength.
[0031] The Ta content is controlled between 30% and 40% to ensure the high density of the material, while avoiding the significant reduction in material activity caused by excessive Ta content. The design of nearly equal atomic ratios of Zr, Ti, and Nb effectively increases the mixing entropy of the material, allowing the material to present the characteristics of a single-phase solid solution.
[0032] The small difference in atomic radius of the alloying elements is conducive to achieving a single-phase solid solution structure and avoiding the brittleness of the material. In addition, the addition of an appropriate amount of V (within 10%) can significantly improve the strength of the material, achieving the characteristics of both high strength and high activity. At the same time, the generation of brittle phases such as intermetallic compounds and Laves phases is avoided, making the high-entropy alloy reaction structure material have good plasticity.
[0033] The main function of an appropriate amount of V element is to improve the strength of the material while avoiding the formation of brittle intermetallic compound phases.
[0034] After designing the composition and ratio of the internal elements of the high-entropy alloy, how to produce high-strength, high-energy content, and high-density high-entropy alloy reaction structural materials becomes the next technical difficulty.
[0035] In order to solve this problem, a method for preparing a high-strength, high-energy, high-entropy alloy reaction structural material is provided below, comprising the following steps: Batching: batching clean Ti element particles, Zr element particles, V element particles, Nb element particles and Ta element particles according to the atomic content ratio; Melting: sending the above ingredients to a magnetic levitation induction melting furnace and melting them in a vacuum environment; Hot isostatic pressing: The cast alloy prepared after smelting is subjected to hot isostatic pressing to obtain a high entropy alloy reaction structural material.
[0036] In this preparation method, magnetic levitation smelting can ensure the cleanliness of smelting and avoid contamination by impurity elements. In order to avoid contamination by impurity elements, further, the purity of the Ti element particles is 99.9%, the purity of the Zr element particles is 99.95%, the purity of the V element particles is 99.9%, the purity of the Nb element particles is 99.95%, and the purity of the Ta element particles is 99.95%; Among them, the above-mentioned metal particles are all clean raw materials for removing oxide scale.
[0037] The elements contained in the above metal particles are calculated by atomic percentage: Ti: 15%-25%; Zr: 15%-25%; V: 0%-10%; Nb: 15%-25%; She: 30%-40%.
[0038] After determining the ratio between the elements, the order of adding materials must be controlled during the smelting process. If the raw materials are added in a random order, a brittle intermetallic compound phase will appear, making it difficult to form a solid solution structure, and the resulting alloy will not meet the requirements. Therefore, in this preparation method, the order of adding raw materials is particularly important.
[0039] Here, when alloy melting is carried out, the raw materials are fed in the following feeding order: First, Ti and Zr elements are synthesized into TiZr master alloy, and Nb and Ta elements are synthesized into NbTa master alloy; Then, the TiZr master alloy, the NbTa master alloy and a small amount of V element are melted to form a single-phase solid solution structure.
[0040] The order of adding materials during the smelting process needs to be controlled to avoid the formation of intermetallic compounds.
[0041] The key and difficulty of this preparation method is to first generate TiZr master alloy and NbTa master alloy separately, and then smelt them with a small amount of V element to form a single-phase solid solution structure.
[0042] The above smelting steps are specifically as follows: -3 The alloy is melted 4-6 times under a vacuum environment of Pa, each melting temperature is between 2200℃ and 2300℃, and each melting time is 15-20 minutes. After the alloy composition is uniform, it is poured into a mold and cooled naturally under a vacuum protection environment.
[0043] The hot isostatic pressing step is carried out in a vacuum or inert gas protected atmosphere, the hot isostatic pressing temperature is 1150-1250° C., and the holding time is 4-6 hours.
[0044] The hot isostatic pressing pressure is 180-200 MPa, the holding time is 4-6 hours, and the cooling rate is 50° C. / min.
[0045] The melting point of this material is about 2100°C. In this method, the hot isostatic pressing temperature is controlled at around 0.5Tm. If the temperature is too low, it will be difficult to eliminate the casting defects. If the temperature is too high, overburning may occur, damaging the initial structure of the material.
[0046] First, it is naturally cooled to form a cast alloy, and then hot isostatic pressing is performed. The main function of hot isostatic pressing is to homogenize the cast alloy and eliminate the segregation of cast elements.
[0047] The following is further described in conjunction with specific embodiments: Embodiment 1: 1) Alloy composition (in terms of atomic percentage): Ti: 20%, Zr: 20%, V: 5%, Nb: 15%, Ta: 40%.
[0048] 2) Preparation method: Batching: the clean Ti element particles, Zr element particles, V element particles, Nb element particles and Ta element particles from which the oxide scale has been removed are batched according to the above atomic percentages; Melting: The above ingredients are sent to the magnetic suspension induction melting furnace. -3 Smelting was performed 4 times in a vacuum environment of Pa, each time at a temperature of 2200°C and for 15 minutes. After the alloy composition was uniform, it was poured into a mold with a diameter of 100 mm and cooled naturally in a vacuum protection environment. When the alloy is smelted, the raw materials are fed in the following order: first, Ti and Zr elements are synthesized into a TiZr master alloy, and Nb and Ta elements are synthesized into a NbTa master alloy; then, the TiZr master alloy and the NbTa master alloy are smelted with a small amount of V element to form a single-phase solid solution structure; Hot isostatic pressing: The cast alloy prepared after smelting is placed in a hot isostatic pressing device protected by inert gas, the pressure is set to 180MPa, the pressure holding time is 4 hours, the temperature is set to 1200℃, the heat preservation is kept for 4 hours, and the cooling rate is 50℃ / min to obtain a high entropy alloy reaction structure material, and the alloy ingot morphology is obtained as follows Figure 1 shown.
[0049] Test method: The density is tested using the Archimedes drainage method.
[0050] According to GB / T23370-2009 and GB / T8167-2008, the alloy prepared above was subjected to quasi-static compression and dynamic compression at room temperature, and static and dynamic deformation critical failure stress tests were performed.
[0051] The test results are shown in the following table: performance Example 1 <![CDATA[Density (g / cm 3 )]]> 10.5 Quasi-static compressive limit stress (MPa) 1750 Quasi-static compressive limit fracture strain (%) 25 Dynamic compressive limit stress (MPa) 2760 Dynamic compressive limit fracture strain (%) 20 The following conclusions can be drawn from the analysis of the above table: The embodiment shows that the density of the high entropy alloy provided by the present invention is 10.0-11 g / cm 3 The quasi-static compressive strength of the material is greater than 1600MPa, the dynamic compressive strength is greater than 2500MPa, the internal organizational structure is uniform, and it has excellent static and dynamic compression strength and plasticity at room temperature.
[0052] The high entropy alloy reaction structural material provided by the present invention can achieve an energy release overpressure value of 0.5 MPa under the impact loading adjustment of a ballistic gun on a 27L closed tank at 1300 m / s.
[0053] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present application. The protection scope of the present application is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present application within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present application.
Claims
1. A high-strength, high-energy, high-entropy alloy reaction structural material, characterized in that: Includes at least two of the elements Ti, Zr, V, Nb and Ta.
2. A high-strength, high-energy, high-entropy alloy reaction structural material according to claim 1, characterized in that: The general formula of the high entropy alloy is TiZrVNbTa, and the content of each element in atomic percentage is as follows: Ti: 0%-25%; Zr:0%-25%; V:0%-15%; Nb: 0%-25%; She: 20%-45%.
3. A high-strength, high-energy, high-entropy alloy reaction structural material according to claim 2, characterized in that: The general formula of the high entropy alloy is TiZrVNbTa, and the content of each element in atomic percentage is as follows: Ti: 15%-25%; Zr:15%-25%; V:0%-10%; Nb: 15%-25%; She: 30%-40%.
4. A method for preparing a high-strength, high-energy, high-entropy alloy reaction structural material, characterized in that: The following steps are involved: Batching: batching clean Ti element particles, Zr element particles, V element particles, Nb element particles and Ta element particles according to the atomic content ratio; Melting: sending the above ingredients to a magnetic levitation induction melting furnace and melting them in a vacuum environment; Hot isostatic pressing: The cast alloy prepared after smelting is subjected to hot isostatic pressing to obtain a high entropy alloy reaction structural material.
5. The method for preparing a high-strength, high-energy, high-entropy alloy reaction structural material according to claim 4, characterized in that: The purity of the Ti element particles is 99.9%, the purity of the Zr element particles is 99.95%, the purity of the V element particles is 99.9%, the purity of the Nb element particles is 99.95%, and the purity of the Ta element particles is 99.95%; Among them, the above-mentioned metal particles are all clean raw materials for removing oxide scale.
6. The method for preparing a high-strength, high-energy, high-entropy alloy reaction structural material according to claim 5, characterized in that: The elements contained in the above metal particles are calculated by atomic percentage: Ti: 15%-25%; Zr:15%-25%; V:0%-10%; Nb: 15%-25%; She: 30%-40%.
7. The method for preparing a high-strength, high-energy, high-entropy alloy reaction structural material according to claim 6, characterized in that: When alloy smelting, the raw materials are fed in the following order: First, Ti and Zr elements are synthesized into TiZr master alloy, and Nb and Ta elements are synthesized into NbTa master alloy; Then, the TiZr master alloy, the NbTa master alloy and a small amount of V element are melted to form a single-phase solid solution structure.
8. The method for preparing a high-strength, high-energy, high-entropy alloy reaction structural material according to claim 7, characterized in that: The above smelting steps are specifically as follows: -3 The alloy is melted 4-6 times under a vacuum environment of Pa, each melting temperature is between 2200℃ and 2300℃, and each melting time is 15-20 minutes. After the alloy composition is uniform, it is poured into a mold and cooled naturally under a vacuum protection environment.
9. The method for preparing a high-strength, high-energy, high-entropy alloy reaction structural material according to claim 8, characterized in that: The hot isostatic pressing step is carried out in a vacuum or inert gas protected atmosphere, the hot isostatic pressing temperature is 1150-1250° C., and the holding time is 4-6 hours.
10. The method for preparing a high-strength, high-energy, high-entropy alloy reaction structural material according to claim 9, characterized in that: The hot isostatic pressing pressure is 180-200 MPa, the holding time is 4-6 hours, and the cooling rate is 50° C. / min.
Citation Information
Patent Citations
Large-size regular billet ingot refractory high-entropy alloy and preparation method thereof
CN110358962A
MoxNbTayTiV high-entropy alloy and preparation method thereof
CN113652593A
Zr-rich high-entropy alloy and preparation method thereof
CN114807714A
Refractory high-entropy alloy with high toughness and high thermal stability at room temperature and preparation method of refractory high-entropy alloy
CN115710667A
